Computer Simulation System for Oscillations of Magnetizable Microdroplets Taking Into Account the Dependence of the Interfacial Tension on the Strength of an External Magnetic Field - Romanenko, M. G.; Shagrova, G. V.; Drozdova, V. I. (Journal of mathematical sciences (New York, N.Y.), 2022)
We present a computer system for simulation of forced oscillations of magnetized microdroplets in alternating magnetic fields taking into account the dependence of the interfacial tension on the external magnetic field obtained from an experiment. Results of computing experiments allow one to identify features of deformation of microdroplets in increasing magnetic fields.